Jangha of the Garbhagriha of the Undeshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The figure installed in the bhadra (central offset) niche of the lateral wall of the garbhagriha (sanctum sanctorum) is particularly noteworthy. This unidentified deity is depicted as if it is moving through the air, with one leg raised backward. Although many of the deity’s multiple arms are broken, the intact hands display a shankha (conch shell) and a chakra (discus) in the front right and left hands, an unidentified object in the middle left hand, and a pushpa (flower) in the upper right hand.